Develoment and Testing of the Technology of Production of the Beebread with the Use of Artificial Combs - Brovarskyi, Valerii; Velychko, Serhii; Brindza, Jan; Adamchuk, Leonora (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Until recently, the main mass of beebread was lost in the process of melting raw and used as material and only its minor portion was used by beekeepers for their own needs. This was mostly due to considerable time to remove beebread from combs as well as bad preservation in the condition of normal environment. However, nowadays with the increase in demand for this kind of product of beekeeping, scientists and practitioners are interested in the development of the technologies of beebread production. The aim of our work was to develop new technological equipment for bee bread production of using artificial comb. Research and construction equipment and its testing were conducted during 2011–2016. The bases of scientific research were “Research Apiary of Holosiievo“ of the Department of Horse-Breeding and Beekeeping of the National University of Life and Environmental Sciences of Ukraine (Ukraine) and Institute of Biodiversity Conservation and Biosafety of the Slovak University of Agriculture in Nitra (Slovak Republic). Approval of new industrial technology was carried out on bee-farms of different forms of ownership in Ukraine. Currently, this technology is patented (no. UA71320) and used by beekeepers in Ukraine. The plastic cartridges were developed, which with the help of holders can be easily connected to each other and forming an artificial comb. One side of the comb is assembled from individual cartridges (435 × 300 mm, 300 × 435 mm, 435 × 230 mm), then a polyethylene Backlit membrane (PET) with the thickness of 0.36 mm is put over and serves as a partition. Then the second side is put over the membrane. The cartridges assembled into the comb are connected to each other with holders. Such comb after filling bee pollen is put into the bee family nest to obtain the beebread. After the comb gets filled with beebread, it is removed from the hive, then the cartridges are separated and the content of the cells is ejected. After ripening of the bee bread for two weeks, comb removed from the hive, the cartridges are then separated and the content of the cells is ejected. We were also designed and constructed manual and mechanized device for bee pollen compression and beebread removing.